2009
DOI: 10.1016/j.atherosclerosis.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Human C-reactive protein induces endothelial dysfunction and uncoupling of eNOS in vivo

Abstract: Background and Objective-Elevated C-reactive protein (CRP) levels are associated with increased cardiovascular events and endothelial dysfunction. We have previously shown that CRP decreases endothelial nitric oxide synthase (eNOS) activity in endothelial cells and inhibits endothelium-dependent nitric oxide (NO)-mediated vasodilation in-vitro. Herein, we examined the effect of in-vivo administration of CRP on endothelial function and underlying mechanisms in a valid animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 47 publications
5
93
0
5
Order By: Relevance
“…dothelial nitric oxide synthase (eNOS) activity. [17][18][19][20][21] In addition, CRP downregulates the number of endothelial progenitor cells and cell function in vitro. 22) The long pentraxin PTX3 shares some similarities with CRP, but differs in terms of structural domain, gene organization, cellular and tissue sources, inducing stimuli, and recognized ligands.…”
Section: Discussionmentioning
confidence: 99%
“…dothelial nitric oxide synthase (eNOS) activity. [17][18][19][20][21] In addition, CRP downregulates the number of endothelial progenitor cells and cell function in vitro. 22) The long pentraxin PTX3 shares some similarities with CRP, but differs in terms of structural domain, gene organization, cellular and tissue sources, inducing stimuli, and recognized ligands.…”
Section: Discussionmentioning
confidence: 99%
“…HMGA1 has been extensively studied as a transforming factor linking viral infection and other perturbations to cancer (reviewed in Reference 35) and HMGA1 is also highly proinflammatory in ECs in response to viral infection (36). The increase in NOS3 expression may reflect uncoupling of NO and peroxynitrite production seen with elevated thromboxane (37) and with inflammation (38). Up-regulation of the NOS3 transcript may represent an attempt to make up for reduced levels of the NOS3 protein in PAH as has been recently shown (39).…”
Section: Discussionmentioning
confidence: 99%
“…Since by searching the literature we could not find similar study we could not compare our results with results of other authors. Possible explanation for obtained results might be proven effect of CRP on inhibition of eNOS in experimental studies (Singh et al 2007, Hein et al 2009). Results of these studies have shown that CRP inhibits GTP cyclohydrolase 1 and stimulates NADPH oxidase which induces decrease of tetrahydrobiopterin and increase of reactive oxygen species resulting in decreased activity of eNOS and consequently decreased bioavailability of NO.…”
Section: Resultsmentioning
confidence: 99%